Reservoir Properties of the Upper Oligocene-Lower Miocene Ibrahim Formation in the Garmian Area, Iraqi Kurdistan Region - Dler H. Baban; Shadan M. Ahmed (Tikrit Journal of Pure Science)
Reservoir characteristics of the Upper Oligocene-Lower Miocene Ibrahim Formation has been studied from the well Hasira-1 (H-1) at Sarqala Oilfield and from the well Taza-3 (Tz-3) at Taza Oilfield in Garmian Area/ southeast Kirkuk City in the Iraqi Kurdistan Region. The available conventional wireline log data are used for detecting the dominant lithology of the formation which appeared to be limestone and argillaceous limestone. The formation in the well H-1 contains appreciable quantity of shale which in some horizons exceeded 35%. The formation is of poor porosity (5% and 8% as average porosity in the well H-1 and Tz-3 respectively) and of poor to fair permeability with an average of 1.9mD in the well H-1. The formation divided to five reservoir units depending on variations in the shale content, porosity and permeability in the well H-1. RU-2 and RU-4 at depth intervals 4125-4128m and 4109-4114m respectively are of relatively the highest reservoir quality among the five recognized reservoir units in the formation. Light hydrocarbons are exist along the Ibrahim Formation in the well H-1 with no effective movability for to be recovered. The examined 17 core samples of the formation in the well Taza-3 is lithologically composed of argillaceous and marly limestone which represented by planktonic foraminifera bearing packstone microfacies. The average porosity of the tested core plug samples of the formation in the well Tz-3 is about 5%, so the formation in this well is of poor reservoir quality as it is in the well H-1.